Fish Bone Foreign Body: The Role of Imaging - Klein,Ayala (2019)
Abstract Introduction Fish bone foreign body (FFB) impaction in the upper aerodigestive tract is a common cause for emergency department referral. Its management varies in both diagnosis and treatment paradigms. Fish bone foreign bodies are more commonly found in the oropharynx in cases of patients < 40 years old, and in the esophagus in cases of patients > 40 years old. Symptoms are typically non-indicative for the location of the FFB, with the exception of foreign body sensation at/superior to the cervical esophagus. A lack of findings during the physical examination is routinely followed by imaging, with computed tomography (CT) being the preferred modality. In practice, many patients undergo unnecessary imaging studies, including CT scans. Objectives To identify patients with suspected fish bone impaction who do not require CT imaging and can be safely discharged. Data Synthesis We have searched the PubMed database for the following medical subject headings (MeSH) terms: fish bone, fish foreign body AND oropharynx, hypopharynx, esophagus, flexible esophagoscopy, and rigid esophagoscopy. Our search in the English language yielded 32 papers. Case reports were included, since they highlighted rare and serious complications. Conclusion In patients > 40 years old suspected of fish bone impaction, noncontrast CT is recommended and should be urgently performed, even in the presence of ambiguous symptoms. However, in patients < 40 years old presenting within 24 hours from ingestion, imaging has little diagnostic value due to the low probability of esophageal fish bones. For this specific subgroup, in the absence of clinical findings, discharge without imaging studies may be considered safe.